Antimicrobial activity of Acorus calamus (L.) rhizome and leaf extract - Asha Devi, S.; Ganjewala, Deepak (Acta Biologica Szegediensis, 2009)
Antimicrobial activity of Acorus calamus rhizome and leaf extracts obtained with different solvents viz., petroleum ether, chloroform, hexane and ethyl acetate was evaluated. Extracts obtained with ethyl acetate among others were found to be highly effective. Rhizomes and leaf ethyl acetate extracts exhibited pronounced antifungal activity with diameter zone of inhibition ranged from 20-28 and 18-25 mm as well as antiyeast activity with diameter zone of inhibition ranged from 22-25 and 20-23 mm, respectively. The minimum inhibitory concentration (MIC) of the rhizome and leaf extracts for antifungal activity measured was 2-4mg/ml, except Penicillium chrysogenum whereas against yeasts was relatively higher, 4-5 and 6-8 mg/ml. MIC value for antibacterial activity was comparatively very high 16-42 mg/ml. In addition, authentic α- and β-asarones were also tested for their antimicrobial potential. Both α- and β-asarones exhibited very strong antimicrobial activities against the fungi and yeasts than those of rhizome and leaf extracts. The study clearly suggested that A. calamus rhizomes and leaves must possess active principle α- and β-asarones which is believed to be responsible for their antimicrobial activities. Both rhizomes and leaf extracts, however, had no antibacterial activity except E. coli.